BIBLIOMETRIC BIBLIOMETRIC ANALYSIS OF MSME DIGITALIZATION AND FINANCIAL LITERACY FOR EFFORTS TO INCREASE POST-PANDEMI INCOME IN 2018-2023 - Cintia Arruum Khalmayati (Media Bisnis, 2023)
Knowledge of financial literacy is an important aspect of life. In practice, there are several advantages that are obtained by MSMEs due to increased knowledge and ability to manage a business better. Apart from being able to boost financial benefits through increasing online sales and providing benefits for buyers with the opportunity to save costs, what is equally important is that MSME financial literacy will also open new spaces that can prevent MSME actors from collapsing in the economic crisis. This study aims to analyze scientific articles to map MSME digitization research and financial literacy by theme, location and research subject as well as the research methods used. This type of research is a qualitative approach. The research data collected in this study from the Google Scholar citation web page used the Harzing's Publish or Perish application. The results showed that the years 2018-2023 were indexed on Google Scholar the highest in 2022 which reached 467 publications (47.08%) . The most publications by type of article are as many as 929 (93.65%). The growing public awareness and need for understanding financial literacy is one of the factors in increasing financial literacy research.